NUTRITIONAL EVALUATION OF LEAVES OF BOERHAAVIA DIFFUSA L. AND ANDROGRAPHIS PANICULATA (BURM.F.)WALL. EX NEES: IMPLICATIONS FOR NUTRACEAUTICAL APPLICATIONS - VINITA PURANIK; DURGESH KUMAR TRIPATHI; DEVINDER KAUR; DEVENDRA KUMAR CHAUHAN (International Journal of Pharma and Bio Sciences, 2012)
Fresh leaves of Boerhaavia diffusa and Andrographis paniculata were evaluated for nutritional and anti-nutritional compositions. The results showed that both plant leaves contained saponins, alkaloids and flavonoids. The proximate analysis and vitamin C of B. diffusa and A. paniculata included moisture (76.04% and 73.02%), carbohydrate (17.14% and 12.16%) and vitamin C (40.00 and 45.01mg/100g), respectively. The mineral contents of the B. diffusa and A. paniculata leaves were found to be P (151.45 and 250.13mg/100g), Na (160.21 and 152.50mg/100g), Ca (218.24 and 318.62mg/100g) and Mg (8.93 and 7.68 mg/100g) respectively. The vitamin and mineral compositions obtained from the analysis suggested that the leaves of these two plants are a good source of vitamin C where as the presence of macro-and micro-nutrients in both the plants leaves make them strongly suitable to be incorporated into human nutrition. The presence of phytochemicals and vitamin C also suggested the anti-oxidant property of these two medicinal plants.